Acute dissection of a syphilitic saccular aneurysm of the ascending aorta and arch in a hypertensive patient - a rare phenomenon - Daisley, Hubert; George, Dennecia; Daisley, Johann (Autopsy and Case Reports, 2024)
We report the case of a 77-year-old male who suffered from hypertension and died suddenly. At autopsy, he was found to have hypertensive cardiomegaly and a dissecting syphilitic saccular aneurysm of the ascending aorta and arch with tamponade. Chronic aortic regurgitation, which is often seen in syphilitic aortitis, produces an additive effect to the concentric left ventricular hypertrophy seen in hypertension.